High-gain lithium niobate brillouin laser with tunable phonon frequency of 1∼31 GHz - Liu, Huibo; Yu, Yu; Li, Kai; Yu, Hengzhe; Wu, Di; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2024)
Stimulated Brillouin scattering (SBS) is a significant nonlinear optical phenomenon utilized across various fields. Its applications span optical sensing, microwave photonics, and all-optical signal processing. In the current information-driven era, the laser industry is imposing increasingly stringent demands on laser technologies, thus propelling integrable on-chip SBS devices into a pivotal research trajectory. Simultaneously, the quest for materials manifesting heightened SBS effects has emerged as a primary focal point in optical fiber transmission endeavors. Lithium niobate (LN) stands out as a promising nonlinear optical material endowed with numerous exemplary attributes. These encompass a high refractive index, fostering potent photon-phonon interactions, low loss characteristics, and high integration potential. Consequently, employing LN as a material for Brillouin lasers promises to enhance certain aspects of laser performance and enable more comprehensive research into Brillouin lasers. In this paper, a micro-ring waveguide structure with LN as the main material is constructed, and the forward gain of stimulated Brillouin scattering, the distribution of electric field in multiple modes and the maximum tunable range are further analyzed. The simulation results exhibit that the tunable forward SBS effect can be achieved in the LN optical waveguides, the maximum forward Brillouin gain can reach 1.34𝑊 -1 𝑚 -1 . Additionally, the tunable phonon frequency can range from 1GHz to 31GHz, effectively doubling that of silicon ring waveguides and thus extending the range of phonon tunability. Therefore, the LN micro-ring waveguide structure provides a new reference direction for the construction of a new tunable laser and a new idea for the generation of lasers to find a Brillouin medium with high SBS effect.